Attention Crisis in Education: An Analysis of Declining Student Focus in the Age of Digital Distractions - David Darwin (Ludi Litterarri, 2026)
The pervasive integration of digital technologies into educational environments has given rise to a significant attention crisis among students at multiple levels of schooling. This article presents a systematic analysis of the factors contributing to the decline in student focus, drawing upon an extensive review of peer-reviewed literature published between 2021 and 2026. The study adopts a qualitative systematic literature review methodology, synthesising findings from 27 empirical and theoretical studies retrieved from Google Scholar using structured search protocols. The analysis reveals that digital distractions—encompassing social media notifications, multitasking behaviours, smartphone use during instruction, and the cognitive demands of digital content—substantially undermine sustained attention, reduce academic engagement, and impair learning outcomes. Digital cognitive overload and the 'brain rot' phenomenon are identified as emerging constructs that characterise modern attentional deficits in educational settings. Findings further indicate that inequalities in attention regulation are mediated by students' digital literacy and socioeconomic background. The article concludes with a framework of evidence-based pedagogical and institutional strategies for restoring attentional capacity, including mindful technology integration, attentional literacy curricula, and structured digital-free learning periods. These findings carry substantial implications for curriculum designers, educators, and educational policymakers seeking to create focused, high-quality learning environments in digitally saturated contexts.